Children reading pictures interpreting visual texts - Arizpe, Evelyn 1965-; Styles, Morag (RoutledgeFalmer, 2003)
This text describes the results of a two-year study of children's responses to contemporary picturebooks. Children of primary school age, from a range of backgrounds, read and discussed books by artists, Anthony Browne and Satoshi Kitamura.
Keywords: Kinderen; Kindertekeningen; Leren; Strips (teksten); Tekstinterpretatie; Kind; Children -- Books and reading; Pictures in education; Visual learning; Bilderbuch; Leseunterricht; Unterricht; Visuelles Lernen; Rezeption